Identification of Skull Base Fracture Complications - Estie R.I. Putri; Eko Prasetyo; Angelica M. J. Wagiu (Universitas Sam Ratulangi, 2022)
Abstract: Fracture of skull base often occurs in traumatic brain injury (TBI) cases and is one of the leading causes of high morbidity and mortality. It can extend beyond the base of the front, middle, or back cranial fossa and cause various complications according to the location of the fractures. This study aimed to identify the complications in cases of fractures of the skull base. This was a literature review study using three databases, as follows: Google Scholar, ClinicalKey and PubMed. The results obtained 30 articles that met the inclusion and exclusion criteria. Complications of vascular injury, intraorbital injury, cerebrospinal fluid (CSF) rhinorrhea could lead to further complications such as meningitis and anosmia in fractures of the front part of skull base; vascular injury, CSF otorrhoea, vertigo, sensorineural or conductive deafness, injuries of II-VIII nerves, and Horner's syndrome in fractures of the middle part of skull base; and vascular injury, nerve injury IX-XII, and cervical injury to coma in fractures of the back part of the skull base. In conclusion, there are a variety of complications that could occur in skull base fractures depending on the location of the fractures.Keywords: complications; skull base fractures; traumatic brain injury (TBI)Â Abstrak: Patah tulang dasar kepala sering terjadi pada penderita cedera otak akibat trauma (COT), dan merupakan salah satu penyebab morbiditas dan mortalitas terbanyak. Patah tulang dasar kepala yang terjadi dapat meluas melewati dasar fossa kranial bagian depan, tengah atau belakang dan menyebabkan berbagai komplikasi sesuai dengan lokasi terjadinya fraktur. Penelitian ini bertujuan untuk mengidentifikasi komplikasi yang dapat terjadi pada kasus patah tulang dasar kepala. Jenis penelitian ialah suatu literature review. Literatur diperoleh melalui tiga database yaitu Google Scholar, ClinicalKey, dan PubMed. Hasil penelitian mendapatkan 30 artikel yang memenuhi kriteria inklusi dan eksklusi. Terdapat komplikasi cedera vaskuler, cedera intraorbita, rhinorrhea cerebrospinal fluid (CSF) hingga menyebabkan komplikasi lanjutan seperti meningitis dan anosmia pada patah tulang dasar kepala bagian depan; cedera vaskuler, otorrhea CSF, vertigo, ketulian konduktif/sensorineural, cedera nervus II-VIII dan sindrom Horner pada patah tulang dasar kepala bagian tengah; dan cedera vaskuler, cedera nervus IX-XII, cedera servikal hingga koma pada patah tulang dasar kepala bagian belakang. Simpulan penelitian ini ialah komplikasi yang terjadi pada kasus patah tulang dasar kepala berbeda-beda tergantung dengan lokasi terjadinya patah tulang.Kata kunci: komplikasi; patah tulang dasar kepala; cedera kepala akibat trauma